2007
DOI: 10.1002/hep.21994
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger receptor class B type I is a key host factor for hepatitis C virus infection required for an entry step closely linked to CD81

Abstract: Hepatitis C virus (HCV) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
248
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 226 publications
(256 citation statements)
references
References 46 publications
7
248
1
Order By: Relevance
“…3 Three lipid transport molecules on the hepatocyte surface have been implicated in viral entry: Low-density lipoprotein (LDL) receptor mediates cellular uptake of HCV RNA, but may be nonessential for productive infection. 4 Scavenger receptor class B type I (SR-BI) is essential for HCV infection in vitro 5 and is discussed in more detail below. Finally, Niemann-Pick C1-like 1 (NPC1L1) has been shown to support HCV entry, but its exact role is, as yet, unclear.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3 Three lipid transport molecules on the hepatocyte surface have been implicated in viral entry: Low-density lipoprotein (LDL) receptor mediates cellular uptake of HCV RNA, but may be nonessential for productive infection. 4 Scavenger receptor class B type I (SR-BI) is essential for HCV infection in vitro 5 and is discussed in more detail below. Finally, Niemann-Pick C1-like 1 (NPC1L1) has been shown to support HCV entry, but its exact role is, as yet, unclear.…”
mentioning
confidence: 99%
“…10,[12][13][14][15] First proposed as an HCV receptor because of its interaction with the viral glycoprotein, E2, 16 SR-BI was subsequently shown to be essential for HCV entry in numerous studies. 5,9,17,18 Animal data indicate that SR-BI is also important for HCV infection in vivo, 19 and an inhibitor of HCV/SR-BI interaction is the only HCVentry inhibitor currently in clinical trials. 20 Recent work has suggested that SR-BI fulfils at least two distinct functions during viral entry: one related to initial attachment and another during post-binding.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that the viral envelope glycoproteins E1 and E2 interact with these four (co)receptors sequentially and that these interactions are orchestrated by cell signaling processes (6,14,28). SR-BI may act early and the tight junction components may act later in this process (11,13,21,24,42). The exact mechanisms and sequence of the interactions remain to be determined, but the result is known to be the uptake of the virion or a virion-coreceptor complex into an endosomal compartment.…”
mentioning
confidence: 99%
“…SR-BI has been shown to interact with the soluble E2 protein with high affinity and its implication as an HCV entry factor is well documented (Bartosch et al, 2003;Dreux et al, 2009;Maillard et al, 2006;Scarselli et al, 2002;Voisset et al, 2005;von Hahn et al, 2006). Interestingly however, HDLs do not appear to compete with HCV entry but rather favor it (Voisset et al, 2005;Zeisel et al, 2007). Recently SR-BII, a form generated by alternative splicing of SR-BI gene, has been shown to bind E2 and to be involved in HCV cell entry as well.…”
Section: Hcv Cellular Entrymentioning
confidence: 99%